The Correspondence of Henry James and the House of Macmillan, 1877–1914
XXVI, 256 p.
Keywords: This is the first book to collect nearly all of the extant correspondence between Henry James and Macmillan in London and, to a lesser degree, in New York. The letters, chiefly between James and Frederick Macmillan over a period of thirty-seven years, deal primarily with business matters, but they also include comment on literary and social affairs. The editorial apparatus seeks to provide context and information sufficient to make the letters available to an academic as well as a general audience.